MORPHOFUNCTIONAL FEATURES OF VENTRICULAR ARRHYTHMIAS IN PATIENTS WITH POSTINFARCTION CARDIOSCLEROSIS AND ARTERIAL HYPERTENSION, DEPENDING ON THE AFFECTED CORONARY REGION - A. M. Valeeva; N. V. Shlyakhtina; O. S. Volodicheva (Сибирский научный медицинский журнал, 2019)
Acute and chronic perfusion disorders, the presence of hypertension are among the main risk factors for the development of electrical instability of the myocardium, in particular ventricular arrhythmias (VA), the progressive course of which increases the risk of sudden cardiac death. Changes in a number of electro- and echocardiographic indicators are recommended to be considered as predictors of the development of life-threatening arrhythmias. Purpose of the study was to study VA features, myocardial remodeling processed and lipid metabolism in patients with arterial hypertension (AH) and myocardial infarction, depending on the affected coronary region. Material and methods. The study involved 50 patients 40–80 years old with post-infarction cardiosclerosis, AH, ventricular arrhythmias episodes, of which 25 people are patients with atherosclerotic lesions of left coronary artery (LCA), 25 people are with the lesions of right coronary artery (RCA). Exclusion criteria: dilated cardiomyopathy, decompensated valvular defects, arrhythmogenic dysplasia, idiopathic ventricular tachycardia, myocarditis. Research methods: echocardiography, coronary angiography, Holter monitor (24-Hour ECG monitoring), biochemical data. Results and discussion. The tendency to the presence of more pronounced pathological changes of heart rate turbulence due to an increase of turbulence slope, dominance of the sympathetic division of the autonomic nervous system against the background of a significantly larger number of paired ventricular extrasystoles have been revealed in the group of patients with atherosclerotic lesions of LCA. That reflects organic and functional changes in the myocardium. The absence of significant changes in the duration and dispersion of the QT interval of the compared groups confirmed the low informativeness of these criteria in the prediction of the VA. The significantly lower value of interventricular septum thickness, left ventricular myocardial mass, and larger size of the right ventricle (0.15 ms) have been revealed along with the above mentioned changes in the group due to the slightly different course of the AH, myocardial remodeling processes. However, more significant changes in the lipid profile, in particular an increase in the level of total cholesterol and blood triglycerides have been registered in the group of patients with PCA. Conclusion. The more pronounced pathological shift of heart rate turbulence due to the increase of turbulence slope up to 4.4 ms/RR on the background of more paired ventricular extrasystoles has been determined in the defeat of the LCA. The significantly lower value of interventricular septum thickness, left ventricular myocardial mass, and larger size of the right ventricular have been observed in the group of patients with atherosclerotic lesions of the LCA in comparison with group of patients with lesions of the PCA.